Path analysis for seed yield and its component characters in fenugreek (Trigonella foenum-graecum L.) - E V D Sastry, K C Sharma (Journal of Spices and Aromatic Crops, 2008)
Fenugreek (Trigonella foenum-graecum L.) is an important spice crop of Rajasthan. A vastgermplasm collection is maintained at S.K.N. College of Agriculture, Jobner. Two hundredforty lines from this germplasm along with five promising varieties namely RMt-1, RMt-143,UM-144, UM-303 and local check were evaluated in an augmented block design at the researchfarm of S.K.N. College of Agriculture, Jobner on light textured soil. Results indicate that thegenotypes showed significant differences for all the characters under study. All the characterhad more than 80% broad sense heritability but only seed yield per plant, biological yieldand pods per plant had above 50% genetic advance expressed as % of mean. The associationanalysis revealed that the seed yield per plant was significant and positively associated withplant height, primary branches per plant, pods per plant, pod length, seeds per pod andbiological yield at both phenotypic and genotypic levels and with test weight at phenotypiclevel. Further path coefficient analysis revealed that characters such as biological yield, podsper plant and primary branches per plant were the important characters for the selection ofhigh yielding genotypes as they exerted positive direct effect as well as showed positivecorrelation with seed yield at both genotypic and phenotypic levels.